1959
DOI: 10.1172/jci103830
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hemorrhage on Pulmonary Circulation and Respiratory Gas Exchange*†

Abstract: A close relationship between pulmonary ventilation and blood flow exists in the normal functioning of the lungs. Thus, primary alterations in one of these processes are difficult to distinguish from secondary changes in the other. In order to study these two functions in the intact animal, we have separated them by utilizing a technique which allows us to induce alterations in pulmonary blood flow while keeping ventilation constant in rate and tidal volume. This report describes changes observed in the pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
1
1

Year Published

1966
1966
1982
1982

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(26 citation statements)
references
References 48 publications
5
19
1
1
Order By: Relevance
“…2). It has been shown, however, by Bjurstedt & Coleridge (1962) and Gerst, Rattenborg & Holaday (1959) that in the dog, a fall in end-tidal carbon dioxide and an increase in arterial pH occurred when the animals were bled under constant artificial ventilation. The explanation offered by both sets of authors was essentially the same.…”
Section: Resultsmentioning
confidence: 97%
“…2). It has been shown, however, by Bjurstedt & Coleridge (1962) and Gerst, Rattenborg & Holaday (1959) that in the dog, a fall in end-tidal carbon dioxide and an increase in arterial pH occurred when the animals were bled under constant artificial ventilation. The explanation offered by both sets of authors was essentially the same.…”
Section: Resultsmentioning
confidence: 97%
“…G erst el al. [8] and Wahrenbrock el al. [23] have demonstrated that Qs/Qt rises during hemorrhagic shock when lung atelectasis is present, but falls when atelectasis has disappeared.…”
Section: Discussionmentioning
confidence: 95%
“…Gas exchange remained normal, ventilation was increased with an enlarged dead space and veno-arterial shunting was reduced. Pulmonary vascular resistance was not different from the control group.Severe morphological changes have been found in the lungs of dogs submitted to hemorrhagic shock [3,6,9,21 ] but the question remains whether the respiratory function changes in relation to the anatomopathological changes or not [3,6,8,17,26]. The purpose of this study was to compare the pathological picture of the lungs with the respiratory function and pul monary hemodynamics during the acute phase of hemorrhagic shock.…”
mentioning
confidence: 99%
“…It has been shown by Gerst, Rattenborg & Holaday (1959) that there is a close relation in the dog between end-tidal Pco. and arterial blood PCO2 and that this relation has been assumed here.…”
Section: Discussionmentioning
confidence: 98%